Influence Of Cash Flow And Working Capital On Profitability And Stock Prices In Consumer Goods Industry - Nunur Fitri Pratiwi; Dayan Hakim Natigor Sipahutar; Yoyo Sudaryo; Nunung Ayu Sofiati (Eduvest - Journal of Universal Studies, 2024)
In the era of globalization and increasingly intense business competition, companies in various industrial sectors are required to manage their resources efficiently to achieve desired financial goals. The objective of a company is to maximize profits for its survival. Sales are one of the main operational activities of a company and a primary source of revenue. The fluctuating nature of stock prices requires an investor to understand the factors influencing their changes. Factors affecting stock price changes include financial statements and financial ratios.This study uses secondary data, namely the financial statements of Consumer Goods Industry companies in the Food and Beverages sub-sector listed on the Indonesia Stock Exchange (IDX) from 2020-2023. The sampling technique used is purposive sampling, resulting in a total sample of 14 companies. The data analysis technique used in this study is multiple linear regression analysis, preceded by classical assumption tests including normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results of the model fit test show that cash flow and working capital are suitable as explanatory variables for profitability.The hypothesis testing results indicate that cash flow has a positive but not significant effect on profitability, meaning that if cash flow increases, profitability tends to increase. Working capital has a negative but not significant effect on profitability, meaning that if working capital decreases, profitability will increase. The market stock price significantly moderates the relationship between cash flow and profitability, but it does not significantly moderate the relationship between working capital and profitability.